Implementation Of Regional Trade Agreements In North Sumatra From The Perspective Of Positive Law And Islamic Law (Analysis Of The Advantages Of North Sumatra Regional Products - Maryani, Halimatul -; Pagar, Pagar -; Zulham, Zulham - (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2024)
Law is a rule that applies among society which contains orders and prohibitions, norms, sanctions relating to human life and life which are of course integrated with nature, and not only internally (nationally) but also regionally and even internationally since entry into force of international agreements in Indonesia. Local wisdom is a support for the strength of a region, especially North Sumatra, to organize neatly the consequences of the implementation of regional trade agreements in Indonesia. So, this presentation examines the Afta-China regional trade structuring model through strengthening local wisdom in North Sumatra, while also aiming to provide solutions to the Indonesian people, especially the people of North Sumatra, that in terms of regional trade structuring offered in this presentation, it is organized through linkages. local wisdom. This means that with the strength of local wisdom possessed by a region, it can be competitive in regional circles. Therefore, the method used in this paper is an empirical juridical research method which not only analyzes data based on policies, but the research team also conducted interviews with parties related to the research theme in this presentation, which is categorized as agricultural sources as staple food producers. . The aim is to study the implications of regional agreements from the perspective of positive law and Islamic law, especially in North Sumatra